Glyphosate affects the larval development of honey bees depending on the susceptibility of colonies - Vázquez, Diego E. (2018)
Fil: Vázquez, Diego E. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental. Laboratorio de Insectos Sociales. Buenos Aires, Argentina.